2010
DOI: 10.1177/0009922810389170
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse Experts Disagree About the Threshold for Mandated Reporting

Abstract: This study found no consensus in how experts on child abuse interpret reasonable suspicion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Our findings agree with earlier research that has exposed difficulties in confirming suspicions and set thresholds for mandated reporting maltreatment . This is not surprising as even experts on child abuse can vary in their assessment of abuse .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with earlier research that has exposed difficulties in confirming suspicions and set thresholds for mandated reporting maltreatment . This is not surprising as even experts on child abuse can vary in their assessment of abuse .…”
Section: Discussionsupporting
confidence: 92%
“…() have identified several barriers to reporting: Lack of knowledge – Healthcare professionals do not always recognise signs and symptoms of abuse (Berkowitz, ; Jenny et al ., ; Markenson et al ., ), and do not always fully understand mandatory reporting procedures (Ward et al, ). Many professionals may believe that they need strong and clear‐cut evidence in order to report, rather than a reasonable suspicion of maltreatment (Flaherty et al ., ; Levi and Crowell, ; Pietrantonio et al ., ). Concern regarding potential negative consequences for clients – The nature of relationships between paediatricians and children's families and the fear of potential harms to the families caused by the report could be a barrier to reporting (Asnes and Leventhal, ; Bannon and Carter, ; Jones et al ., ). Negative attitudes toward CPS – Health professionals who have had prior negative experiences in dealing with CPS may feel reluctant to report to CPS, believing that involvement of CPS may cause more harm than benefit (Flaherty et al, ; Jones et al ., ). Other clinicians appear reluctant to involve child protection agencies on the basis of their belief that doing so would not be in the best interests of the child's welfare (Bannon and Carter, ).…”
Section: Introductionmentioning
confidence: 99%
“…3 -5 The authors of 1 study showed that even child abuse experts do not agree on where the threshold for reporting lies. 6 Without a specific definition or cutoff for reasonable suspicion, there continues to be variability in reporting practices. 7 There are also numerous reasons that physicians may decide not to make a report, even when there is a suspicion for child abuse.…”
Section: Larissa Hines MD Commentsmentioning
confidence: 99%